Penerapan Corporate Social Responsibility (CSR) pada PT Kereta Api Indonesia (Persero) - Winda Khoirunnisa; Rahma Nazila Muhammad (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determine the implementation of CSR which has received awards from various institutions and how the impact it produces. This research is a case study at PT Kereta Api Indonesia (Persero), the method used is descriptive qualitative with primary and secondary data. The results of the study show that PT KAI focuses its CSR implementation on the priority categories of the Ministry of BUMN. PT KAI's CSR program includes the classification of corporate social marketing, corporate philanthropy, and socially responsible business practice. The impact from the qualitative side, to the community provides technical facilities, protected natural environment, as well as social activation. And to the company produces a reputation and positive image.